An experiential investigation into the embroidery practices of the Chernobyl Babushka. Issue 1 (1st March 2019) - Baker, Claire A.
This article contextualizes and personalizes a cohesive and cogent line of enquiry into the textile practices of the Babushkas of Chernobyl through empirical research centred upon observing, recording and gathering testimonies and histories in the field. Chernobyl, as place (or rather non-place), is the site of the world's worst nuclear accident of 1986. Post-accident, 91, 200 people were evacuated from areas around Chernobyl and it is now deemed to be uninhabitable. At the time of this research, there were 128 people remaining, their legacy the declining remains of a forgotten community, with a loss of their strong textile heritage. The 'Embroidery as a Language' project was implemented in order to discover how a common interest, i.e. embroidery, within the context of action research methodology could be used to encourage stronger connections and understandings between transnational communities and as a consequence promote the sharing of relevant and new information about regional embroidery, in turn preserving the past and taking it forward into the future. Alongside building an archive, the preservation of their history through personal experiences and narratives is paramount and this article reflects the focus on the self-settlers of Chernobyl and their embroideries as an ongoing initiative and an experiential poignant investigation that has developed over the past four years and during my ten separate visits to the Chernobyl Exclusion Zone.